2022
DOI: 10.1002/ece3.9616
|View full text |Cite
|
Sign up to set email alerts
|

Responses in thermal tolerance and daily activity rhythm to urban stress in Drosophila suzukii

Abstract: Cities experience changes in abiotic factors, such as warming, increases in noise and light. These changes can lead to phenotypic changes. Several studies have revealed that altered environments change phenotypes in plants and animals in cities. However, limited studies have isolated evolutionary from nongenetic changes. Here, we analyzed the evolution of thermal tolerance and diurnal activity patterns in the urban population of the fruit pest, Drosophila suzukii . Urban and rural isofem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 96 publications
0
6
0
Order By: Relevance
“…Such high temperatures can have severe ecological impacts on the behavior, physiology, and life history of various organisms, including humans that live in cities (19)(20)(21)(22)(23). While the evolutionary effects of urban heat stress on some animals have begun to be explored (24)(25)(26)(27)(28)(29), the evolutionary impacts on plants have not yet been examined. Plants, which are sessile organisms highly sensitive to environmental stresses related to the ground surface (20,21,30,31), are likely to be under strong selection pressure from urban heat islands.…”
Section: Introductionmentioning
confidence: 99%
“…Such high temperatures can have severe ecological impacts on the behavior, physiology, and life history of various organisms, including humans that live in cities (19)(20)(21)(22)(23). While the evolutionary effects of urban heat stress on some animals have begun to be explored (24)(25)(26)(27)(28)(29), the evolutionary impacts on plants have not yet been examined. Plants, which are sessile organisms highly sensitive to environmental stresses related to the ground surface (20,21,30,31), are likely to be under strong selection pressure from urban heat islands.…”
Section: Introductionmentioning
confidence: 99%
“…This study highlights the importance of species' thermal physiology in shaping community compositions through functional filtering processes. This importance is also supported by the large number of studies focusing on intraspecific variation in thermal tolerance [47][48][49][50][51]. An alternative explanation for the observed change in community-averaged thermal affinities could be an indirect effect of body size, through the covariation of species' thermal affinity and body size.…”
Section: Relationships Between Functional Traits and Environmental Co...mentioning
confidence: 83%
“…The thermal affinity of species is also expected to be an important functional trait driving species community composition at local and landscape scales [7]. If many studies have examined intraspecific changes in critical thermal limits [47][48][49][50][51] and thermal preferences [52] along UHI gradients, almost no studies have considered interspecific thermal traits to test whether changes also occur at the community level. Although a few studies have reported changes in thermal affinities of urban versus rural communities in ants and carabids [7,53], the identification of explanatory variables remains to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was also argued that streetlamp light was a source of light pollution for the night landscape [ 36 , 37 ]. This was partly identified because night light impaired the sustainable development of the habitats and community activities of urban animals, such as bats [ 38 ], birds [ 39 ], flies [ 40 ], crickets [ 41 ], etc. The impact of night light can be as large as it is remarkable in urban ecosystems that are supported by green spaces with greeneries [ 42 ].…”
Section: Introductionmentioning
confidence: 99%